Exploring A Decade of Research on Down Syndrome: A Bibliometric Analysis - J George, Rinu; Kumar L, Manoj; Deepa T Unnikrishnan; Kunjavara , Jibin; Shiny T Sam (National Journal of Community Medicine, 2024)
Aims: Trisomy 21, the presence of a supernumerary chromosome 21, results in a collection of clinical features commonly known as Down syndrome (DS). DS is among the most genetically complex of the conditions that are compatible with human survival post-term, and the most frequent survivable autosomal aneuploidy. The research landscape of Down Syndrome is not portrayed clearly by published literature. This study aimed to analyse published literature globally by the medical fraternity in the field of Down syndrome using bibliometric analysis. Methodology: Bibliometric information on literature regarding said topic using specific keywords was searched and collected in the Scopus database. VOSviewer (1.6.18) was applied to conduct bibliometric analysis and visualization. Results: The study highlighted the most significant journals, authors, co-cited authors, institutions, keywords co-occurrence, and most contributed countries in the area of Down syndrome based on bibliometric analysis of studies taken from the database of Scopus for the past ten years (2014–first quarter of 2023). Conclusion: This analysis applied state-of-the-art bibliometric and scientific mapping methods to provide researchers and other stakeholders with a panoramic view of Down syndrome from 2014 –2023. Publications in the field show a stable trend, within developed countries. Funding support is much needed to proceed with such topics as Down syndrome and that may be the reason why underdeveloped countries are still behind in the field.